Bufotalin Induces Oxidative Stress-Mediated Apoptosis by Blocking the ITGB4/FAK/ERK Pathway in Glioblastoma - Junchao Tan; Guoqiang Lin; Rui Zhang; Yuting Wen; Chunying Luo; Ran Wang; Feiyun Wang; Shoujiao Peng; Jiange Zhang (MDPI AG, 2024)
Bufotalin (BT), a major active constituent of Chansu, has been found to possess multiple pharmacological activities. Although previous studies have shown that BT could inhibit the growth of glioblastoma (GBM), the safety of BT in vivo and the potential mechanism are still unclear. We conducted a systematic assessment to investigate the impact of BT on GBM cell viability, migration, invasion, and colony formation. Furthermore, in vivo results were obtained to evaluate the effect of BT on tumor growth. The preliminary findings of our study demonstrate the effective inhibition of GBM cell growth and subcutaneous tumor development in mice by BT, with tolerable levels of tolerance observed. Mechanistically, BT treatment induced mitochondrial dysfunction, bursts of reactive oxygen species (ROS), and subsequent cell apoptosis. More importantly, proteomic-based differentially expressed proteins analysis revealed a significant downregulation of integrin β4 (ITGB4) following BT treatment. Furthermore, our evidence suggested that the ITGB4/focal adhesion kinase (FAK)/extracellular signal-related kinase (ERK) pathway involved BT-induced apoptosis. Overall, our study demonstrates the anti-GBM effects of BT and elucidates the underlying mechanism, highlighting BT as a potential therapeutic option for GBM.